Solubility of phenytoin in aqueous mixtures of ethanol and sodium dodecyl sulfate at 298 k (2014)
The solubility of phenytoin in binary mixtures of ethanol + water at 298.2 K in the presence of three different concentrations of sodium dodecyl sulfate (sds) was reported. The Jouyban-Acree model was used for correlating the generated data and the obtained mean relative deviation was 7.3%. When all data points of phenytoin in binary solvents at various sds concentrations were fitted to the model, the obtained mean relative deviation was 10.1%.